2013
DOI: 10.1080/01425692.2012.714250
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Bernsteinian language of description for mathematics classroom discourse

Abstract: This article aims at developing an external language of description to investigate the problem of why particular groups of students are systematically not provided access to school mathematical knowledge. Based on Basil Bernstein's conceptualisation of power in classification, we develop a three-dimensional model that operationalises the contextual boundaries, the linguistic features and the structure of knowledge, and their respective relations to power on a not too high level of abstraction. The contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…However, none of the interviewees described such development within mathematics. As studies have shown that mathematics is traditionally the subject that has the clearest boundaries, and is identified as strongly classified (Bernstein, 2000;Cause, 2010;Straehler-Pohl & Gellert, 2013), this is not surprising. Furthermore, Bleazby (2015) has argued that the integration of different subjects and the implementation of cross-curricular themes has failed to deconstruct the traditional curriculum hierarchy, since integrated subjects shift to a lower position within the subject hierarchy.…”
Section: Breaking the Walls: Teamwork And Integration Of Subjectsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, none of the interviewees described such development within mathematics. As studies have shown that mathematics is traditionally the subject that has the clearest boundaries, and is identified as strongly classified (Bernstein, 2000;Cause, 2010;Straehler-Pohl & Gellert, 2013), this is not surprising. Furthermore, Bleazby (2015) has argued that the integration of different subjects and the implementation of cross-curricular themes has failed to deconstruct the traditional curriculum hierarchy, since integrated subjects shift to a lower position within the subject hierarchy.…”
Section: Breaking the Walls: Teamwork And Integration Of Subjectsmentioning
confidence: 97%
“…Scholars have argued that such high status disciplines with vertical knowledge structures are identified with strong classification (Bleazby, 2015) and that classification is especially strong between mathematics and other subjects (Cause, 2010). Research has shown that natural science programmes tend to attract high achieving students from strong social backgrounds (Beach, 2008;Hjelmér, 2011;Weis, Cipollone, & Jenkins, 2014), and that mathematics in particular is known to be a gatekeeper to higher studies and well paid jobs in society (Arnot & Reay, 2004;Lynch & McGarr, 2016;Straehler-Pohl & Gellert, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Straehler-Pohl and Gellert (2013) have taken the boundary discussion further. They use the concept gaps, and argue that these are crucial to the understanding of Bernstein’s classification.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Att koordinera socialsemiotik med Bernsteins teorier har gjorts även i andra studier (t.ex. Dimopoulos, Koulaidis, & Sklaveniti, 2005;Straehler-Pohl & Gellert, 2012).…”
Section: Tre Metafunktioner Inom Socialsemiotikunclassified